2008
DOI: 10.1093/mp/ssm007
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid, High-Light, and Oxidative Stress Down-Regulate a Photosynthetic Gene via a Promoter Motif Not Involved in Phytochrome-Mediated Transcriptional Regulation

Abstract: In etiolated seedlings, light perceived by phytochrome promotes the expression of light-harvesting chlorophyll a/b protein of photosystem II (Lhcb) genes. However, excess of photosynthetically active radiation can reduce Lhcb expression. Here, we investigate the convergence and divergence of phytochrome, high-light stress and abscisic acid (ABA) signaling, which could connect these processes. Etiolated Arabidopsis thaliana seedlings bearing an Lhcb promoter fused to a reporter were exposed to continuous far-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 42 publications
2
79
0
Order By: Relevance
“…It binds to the CCAC core motif in promoters of lightand ABA-responsive genes [31] and mutations in this motif affect ABA-, high light-and H 2 O 2 -dependent gene regulation [32]. Hence, ABI4 integrates ROS and ABA signaling at the transcriptional level.…”
Section: Priming Of Early Post-invasive Penetration Resistancementioning
confidence: 99%
“…It binds to the CCAC core motif in promoters of lightand ABA-responsive genes [31] and mutations in this motif affect ABA-, high light-and H 2 O 2 -dependent gene regulation [32]. Hence, ABI4 integrates ROS and ABA signaling at the transcriptional level.…”
Section: Priming Of Early Post-invasive Penetration Resistancementioning
confidence: 99%
“…Other attempts to show that gun mutants are resistant to norflurazon were not successful [26,44,45]. Indeed, ROS and blocking chloroplast biogenesis with norflurazon appeared to activate distinct plastid-to-nucleus signalling mechanisms [44,46].…”
Section: The Gun Mutant Screenmentioning
confidence: 99%
“…Light and plastid signals appear distinct because plastid signals can regulate PhANG expression in the dark [5,19,48]. Plastid-to-nucleus signalling that is activated by chloroplastic ROS uses distinct promoter elements from those activated by blocking chloroplast biogenesis with norflurazon treatments [46].…”
Section: Integration Of Light and Plastid-to-nucleus Signallingmentioning
confidence: 99%
“…Moreover, lighting conditions might evoke the photoxidative changes in plants, which lead to the altered action of the antioxidant defense system: increased contents and activity of antioxidative enzymes, carotenoid, tocopherol, flavonoid and ascorbate. It is known how the light irradiance level affects different plants [18,19], although the knowledge regarding the effect of light spectral quality for metabolism is still limited. It has been demonstrated that exposure to light-emitting diodes (LED) radiation can increase the antioxidant activity in pea seedlings [20] and the phenolic content in buckwheat sprouts [21].…”
Section: Introductionmentioning
confidence: 99%